2014
DOI: 10.1177/0954406214521793
|View full text |Cite
|
Sign up to set email alerts
|

Design and test of vehicle suspension system with inerters

Abstract: A vehicle suspension system with inerters is proposed and its dynamic model is established to analyse its dynamic performance. The structure of the suspension with inerters is also constructed and its form and structural parameters are optimized. Then the rack-and-pinion inerter and the bench test system of suspension are designed. Based on the simulation, bench test is conducted. It has shown that theoretical research is consistent with the test results. Moreover, the structure of the suspension with inerters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 11 publications
0
13
0
Order By: Relevance
“…The global coordinates of the characteristic points (except those coordinates that are independent parameters: Z Gs , or Z Gs and Z Gd ) are the unknowns, which appear explicitly in equations (3), while in equation 4they appear as implicit through the global coordinates of the guiding points (X Mi , Y Mi , Z Mi ). Within the general nonlinear system given in equations (3) and (4), the three-equation system given in equations (2), which describes the correlations among the global coordinates of the guiding points and those of the characteristic points, was solved in closed form as the solution of the quadratic equation by subtracting the first equation from the other two, similar to the procedure described in Alexandru et al 15 The obtained nonlinear system is then solved by using the Newton-Kantorovich method. The initial solution corresponds to the vehicle rest position, while for the current position of the mechanism, the initial solution is that obtained in the previous position; in this way, the spatial positioning of the mechanism can be determined for the complete vertical travel field of the wheel(s), defined by the field(s) of variation in the independent parameter(s).…”
Section: The Kinematics Of the Guiding Mechanismmentioning
confidence: 99%
See 1 more Smart Citation
“…The global coordinates of the characteristic points (except those coordinates that are independent parameters: Z Gs , or Z Gs and Z Gd ) are the unknowns, which appear explicitly in equations (3), while in equation 4they appear as implicit through the global coordinates of the guiding points (X Mi , Y Mi , Z Mi ). Within the general nonlinear system given in equations (3) and (4), the three-equation system given in equations (2), which describes the correlations among the global coordinates of the guiding points and those of the characteristic points, was solved in closed form as the solution of the quadratic equation by subtracting the first equation from the other two, similar to the procedure described in Alexandru et al 15 The obtained nonlinear system is then solved by using the Newton-Kantorovich method. The initial solution corresponds to the vehicle rest position, while for the current position of the mechanism, the initial solution is that obtained in the previous position; in this way, the spatial positioning of the mechanism can be determined for the complete vertical travel field of the wheel(s), defined by the field(s) of variation in the independent parameter(s).…”
Section: The Kinematics Of the Guiding Mechanismmentioning
confidence: 99%
“…The suspension system plays a crucial role in the comfort, handling and stability performance of road vehicles; optimal suspension design, including the development of innovative solutions such as those proposed in Soong et al 1 and Wang et al, 2 is always a concern and challenge. For vehicles with two axles, the design of the front suspension is different from that of the rear suspension.…”
Section: Introductionmentioning
confidence: 99%
“…After more than 10 years of development, the structure of an inerter has gradually diversified, including rack-andpinion inerters [11], ball-screw inerters [12], and hydraulic inerters [13]. In [14]- [17], the suspension employing an inerter element performs better than a traditional passive suspension.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al defined four performance indices to evaluate the isolation performance of the inerter‐based vibration isolator and showed that it can achieve a better isolation performance compared with the linear spring–damper vibration isolator. The inerter has also been applied in other structures due to its mechanical property, including vehicle suspension, motorcycle steering system, train suspension, building vibration control system, landing gear, dynamic vibration absorber, and tuned mass damper . The researches show that when the inerter is used, these mechanical systems can achieve a superior performance.…”
Section: Introductionmentioning
confidence: 99%